Theoretical Calculation of Vector Correlations for the Reaction (Communications in Computational Chemistry, 2025)
The stereodynamics of the reaction $H(^2S) + NH$ $(v= 0, 1, 2, 3; j = 0)→$$N(^4S) + H_2$ are studied using the quasi-classical trajectory method on a double many-bodyexpansion potential energy surface to understand the alignment and orientation of theproduct molecules in the collision energy range of 2–20 kcal·${\rm mol}^{−1},$ The vibrational–rotational quantum number of the NH molecules is specifically investigated for $v = 0, 1,2,$ and $3$ and $j = 0.$ The $P(\theta_r),$ $P(\phi_r ),$ $P(\theta_r ,\phi_r ),$ differential cross section [DCS; ($2\pi\sigma)$$(d\sigma_{00}/dw_t)],$ and average rotational alignment factor $〈P_2({\rm cos}\theta_r)〉$ are calculated. Thestereodynamics results indicate that the reagent vibrational quantum number andinitial collision energy significantly affect the distributions of the $k–j',$ $k–k'–j'$ and $k–k'$ vector correlations along with $〈P_2({\rm cos} \theta_r)〉.$ In addition, while DCS is extremelysensitive to the collision energy, it is not significantly affected by the vibrationalexcitation of the reagents.
Keywords: quasi-classical trajectory method; stereodynamics; potential energy surface; vector correlation.